Table_1_Detection and Genetic Characterization of Canine Adenoviruses, Circoviruses, and Novel Cycloviruses From Wild Carnivores in Italy.docx - Linda A. Ndiana; Gianvito Lanave; Violetta Vasinioti; Costantina Desario; Camillo Martino; Maria Loredana Colaianni; Francesco Pellegrini; Antonio Camarda; Shadia Berjaoui; Giovanni Sgroi; Gabriella Elia; Annamaria Pratelli; et al. (2022)
Wild carnivores are known to play a role in the epidemiology of several canine viruses, including canine adenoviruses types 1 (CAdV-1) and 2 (CAdV-2), canine circovirus (CanineCV) and canine distemper virus (CDV). In the present study, we report an epidemiological survey for these viruses in free ranging carnivores from Italy. A total of 262 wild carnivores, including red foxes (Vulpes vulpes), wolves (Canis lupus) and Eurasian badgers (Meles meles) were sampled. Viral nucleic acid was extracted and screened by real-time PCR assays (qPCR) for the presence of CAdVs and CanineCV DNA, as well as for CDV RNA. CAdV-1 DNA was detected only in red foxes (4/232, 1.7%) whilst the wolves (0/8, 0%) and Eurasian badgers (0/22, 0%) tested negative. CanineCV DNA was detected in 4 (18%) Eurasian badgers, 4 (50%) wolves and 0 (0%) red foxes. None of the animals tested positive for CDV or CAdV-2. By sequence and phylogenetic analyses, CAdV-1 and CanineCV sequences from wild carnivores were closely related to reference sequences from domestic dogs and wild carnivores. Surprisingly, two sequences from wolf intestines were identified as cycloviruses with one sequence (145.20-5432) displaying 68.6% nucleotide identity to a cyclovirus detected in a domestic cat, while the other (145.201329) was more closely related (79.4% nucleotide identity) to a cyclovirus sequence from bats. A continuous surveillance in wild carnivores should be carried out in order to monitor the circulation in wildlife of viruses pathogenic for domestic carnivores and endangered wild species.